The temporal scale of diet and dietary proxies. Issue 6 (2nd March 2016) - Davis, Matt; Pineda Munoz, Silvia
Abstract: Diets estimated from different proxies such as stable isotopes, stomach contents, and dental microwear often disagree, leading to nominally well‐supported but greatly differing estimates of diet for both extinct and extant species that complicate our understanding of ecology. We show that these perceived incongruences can be caused by proxies recording diet over vastly different timescales. Field observations reveal a diet averaged over minutes or hours, whereas dental morphology may reflect the diet of a lineage over millions of years of evolution. Failing to explicitly consider the scale of proxies and the potentially large temporal variability in diet can cause erroneous predictions in any downstream analyses such as conservation planning or paleohabitat reconstructions. We propose a cross‐scale framework for conceptualizing diet suitable for both modern ecologists and paleontologists and provide recommendations for any studies involving dietary data. Treating diet in this temporally explicit framework and matching the scale of our questions with the scale of our data will lead to a much richer and clearer understanding of ecological and evolutionary processes. Abstract : Different proxies can return very different estimates of an animal's diet because they record diet over vastly different timescales. We review the effects of temporal scaling on dietary analysis and provide recommendations for using dietary data effectively. With a cross scale framework and multiple proxies, we can infer an animal's diet from seconds to millions of years of evolutionary history.